Mapping AI Literacy and Motivation Trends among College Students in Southeast Asia - Mantua, Wenna Jo; Cagasan-Bulan, Roselyn; Cabradilla, Fiona Bianca; Delmonte, Gloriane (JPAIR Multidisciplinary Research, 2026)
Artificial Intelligence (AI) is reshaping higher education across the globe. However, questions remain on how students are prepared and motivated to adopt AI tools in Southeast Asia. This paper studies the relationship between AI literacy and student motivation, focusing on the cultural and contextual factors that shape adoption and role of ethical awareness. Using an integrative review of peer-reviewed studies and policy reports published between 2018 and 2025, the research brings together regional evidence to highlight emerging patterns and gaps. Results show that students with stronger AI literacy are generally more motivated to use AI in learning, though this relationship is influenced by socio-economic background, institutional resources, and national digital infrastructure. Learners in digitally advanced countries display higher adoption rates, while those in resource-constrained settings face challenges that widen equity gaps. Ethical awareness also plays a critical role when paired with supportive institutional policies as it strengthens motivation and encourages responsible use. The study argues that comprehensive literacy programs, equity-focused initiatives, and ethics-driven curricula are vital for preparing Southeast Asian students to meet the demands of the Fourth Industrial Revolution. By mapping regional trends and pinpointing areas that need attention, this review offers insights that can guide policy, curriculum design, and institutional strategies toward more inclusive and ethical AI integration.